Green or social? An analysis of environmental and social sustainability advertising and its impact on brand personality, credibility and attitude - Frauke Sander; Ulrich Föhl; Nadine Walter; Vera Demmer (Journal of Brand Management, 2021)
The aim of this paper is to examine the impact of sustainability advertising on brand personality, credibility, attitude toward the ad and brand attitude; special attention was given to whether or not environmental and social sustainability advertising have different effects. The results of an online survey revealed that environmental sustainability advertising has a stronger influence than social sustainability advertising. Thus, the findings suggest that a focus on environmental aspects delivers the more impactful advertising content when promoting a brand's sustainability. This result is consistent with the existing studies on the sub-dimensions of sustainability; although only researched in different contexts, earlier findings also showed that environmental sustainability has a higher impact. Furthermore, an explicit integration of environmental aspects into the measurement of brand personalities offers a new and interesting field of future research. The study is based on data collected from 166 respondents. The impact of sustainability advertising is investigated by an experimental manipulation of the advertising condition. To test the hypotheses, structural equation models are applied, as well as one-way analyses of variance.
Keywords: 330; Brand personality; Sustainability advertising; Social sustainability advertising; Environmental advertising; Brand attitude; Credibility